1998
DOI: 10.1128/iai.66.3.1023-1027.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Specific Secretion Rather than Autolysis in the Release of Some Helicobacter pylori Proteins

Abstract: We investigated whether Helicobacter pylori cells actively secrete proteins such as the urease subunits UreA and UreB and the GroES and GroEL homologs HspA and HspB or whether these proteins were present in the extracellular compartment as a consequence of autolysis. Using a subcellular fractionation approach associated with quantitative Western blot analyses, we showed that the supernatant protein profiles were very different from those of the cell pellets, even for bacteria harvested in the late growth phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(67 citation statements)
references
References 32 publications
2
63
1
1
Order By: Relevance
“…The molecular chaperone GroEL was also previously identified as a marker of gastric cancer risk in a German study 8 and is proposed to influence the binding of the bacterium to the gastrointestinal mucosa. 26,27 HcpC belongs to the family of Helicobacter cysteine-rich proteins that induce proinflammatory cytokines 28 and it has previously been associated with chronic atrophic gastritis. 9 While our risk prediction analysis was purely exploratory, it is interesting to note that models using the multiplex data performed relatively well and were in general agreement with results of disease association models.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular chaperone GroEL was also previously identified as a marker of gastric cancer risk in a German study 8 and is proposed to influence the binding of the bacterium to the gastrointestinal mucosa. 26,27 HcpC belongs to the family of Helicobacter cysteine-rich proteins that induce proinflammatory cytokines 28 and it has previously been associated with chronic atrophic gastritis. 9 While our risk prediction analysis was purely exploratory, it is interesting to note that models using the multiplex data performed relatively well and were in general agreement with results of disease association models.…”
Section: Discussionmentioning
confidence: 99%
“…In H. pylori, HspB (GroEL homologue) is released by bacterial autolysis and becomes adsorbed to the surface of intact bacteria in vitro, and this mechanism also seems to be present in vivo when human gastric biopsies are examined [16,17]. On the other hand, Vanet and Labigne [18] concluded that secretion of HspB did not occur by a programmed autolysis process but by a speci¢c and selective mechanism. Signi¢cant enhancement of IL-6 production by C. rectus LPS has been reported [19].…”
Section: Discussionmentioning
confidence: 99%
“…Su⁄cient protein was puri¢ed from P. aeruginosa to carry out a study of immune-speci¢c responses to six proteins of molecular masses equivalent to 13,16,20,40,45 and 80 kDA, as shown in Fig. 1.…”
Section: Puri¢cation and Identi¢cation Of Protein Antigensmentioning
confidence: 99%